A MeerKAT survey of nearby nova-like cataclysmic variables. Issue 3 (22nd June 2020) - Hewitt, D M; Pretorius, M L; Woudt, P A; Tremou, E; Miller-Jones, J C A; Knigge, C; Castro Segura, N; Williams, D R A; Fender, R P; Armstrong, R; Groot, P; Heywood, I; et al.
ABSTRACT: We present the results of MeerKAT radio observations of 11 nearby nova-like cataclysmic variables (CVs). We have detected radio emission from IM Eri, RW Sex, V3885 Sgr, and V603 Aql. While RW Sex, V3885 Sgr, and V603 Aql had been previously detected, this is the first reported radio detection of IM Eri. Our observations have doubled the sample of non-magnetic CVs with sensitive radio data. We observe that at our radio detection limits, a specific optical luminosity 2.2× 10^18 erg s −1 Hz −1 (corresponding to MV ≲ 6.0) is required to produce a radio detection. We also observe that the X-ray and radio luminosities of our detected nova-like CVs are on an extension of the L_XL_R^0.7 power law originally proposed for non-pulsating neutron star low-mass X-ray binaries. We find no other correlations between the radio emission and emission in other wavebands or any other system parameters for the existing sample of radio-detected non-magnetic CVs. We measure in-band (0.9–1.7 GHz) radio spectral indices that are consistent with reports from earlier work. Finally, we constructed broad spectral energy distributions for our sample from published multiwavelength data, and use them to place constraints on the mass transfer rates of these systems.